A Dy2 dimer derived from a two-dimensional network with a high Ueff value. Issue 8 (31st January 2019) - Zhang, Ju-Wen; Man, Yi; Liu, Wen-Hua; Liu, Bin-Qiu; Dong, Yan-Ping
Abstract : A new two-dimensional dysprosium–organic coordination polymer1 -Dy has been synthesized by a hydrothermal method.1 -Dy displays a ferromagnetic interaction between two Dy III ions within the Dy2 dimer and a slow magnetic relaxation with a high effective energy barrier of approximately 160 K under a zero dc field. Abstract : A new Dy2 -dimer-based two-dimensional network Dy(L)(HL)(phen) (1 -Dy) has been synthesized by a hydrothermal method.1 -Dy displays an obvious single-molecule magnet (SMM) behavior with a high U eff value of approximately 160 K under a zero dc field.